Genetics of Tinnitus: An Emerging Area for Molecular Diagnosis and Drug Development - Lopez-Escamez, Jose A.; Bibas, Thanos; Cima, Rilana F. F.; Van de Heyning, Paul; Knipper, Marlies; Mazurek, Birgit; Szczepek, Agnieszka J.; Cederroth, Christopher R. (Frontiers in Neuroscience, 2016)
Subjective tinnitus is the perception of sound in the absence of external or bodily-generated sounds. Chronic tinnitus is a highly prevalent condition affecting over 70 million people in Europe. A wide variety of comorbidities, including hearing loss, psychiatric disorders, neurodegenerative disorders and temporomandibular joint dysfunction, have been suggested to contribute to the onset or progression of tinnitus, however the precise molecular mechanisms of tinnitus are not well understood and the contribution of genetic and epigenetic factors remains unknown. Human genetic studies could enable the identification of novel molecular therapeutic targets, possibly leading to the development of novel pharmaceutical therapeutics. In this article, we briefly discuss the available evidence for a role of genetics in tinnitus and consider potential hurdles in designing genetic studies for tinnitus. Since multiple diseases have tinnitus as a symptom and the supporting genetic evidence is sparse, we propose various strategies to investigate the genetic underpinnings of tinnitus, first by showing evidence of heritability using concordance studies in twins, and second by improving patient selection according to phenotype and/or etiology in order to control potential biases and optimize genetic data output. The increased knowledge resulting from this endeavor could ultimately improve the drug development process and lead to the preventive or curative treatment of tinnitus.